The Ghost in the Red Shirt - Bower, B. M., 1871-1940 (Salt Lake City, UT : Project Gutenberg, 2022)
"The Ghost in the Red Shirt" by B. M. Bower is a short story written in the early 20th century. This whimsical narrative intertwines elements of humor and ghostly intrigue, centering around the experiences of a group of individuals caught in a mysterious situation while seeking shelter from a storm in an old cabin. Through the lens of the protagonist, the story explores themes of love, friendship, and the supernatural, ultimately questioning the nature of belief in ghosts. The story follows a group of six individuals$1 (Bfeaturing Aunt Jane, Cousin Jack, Mabel, Professor Goldburn, and Clifford Wilton$1 (Bwho find themselves stranded in a cabin after their boat capsizes. As they sit around a fire to keep warm, they encounter a ghostly figure dressed in a red flannel shirt. The protagonist, fascinated and mildly terrified, observes the varied reactions of her companions to the apparition$1 (Bwhile she finds it discomforting, some, like Clifford, seem more intrigued. The narrative culminates in a series of humorous exchanges and unexpected events that add to the charm of the tale, ultimately leaving the reader to ponder the reality of the ghost's presence while illustrating the protagonist's evolving relationship with Clifford, resulting in a budding romance amid the eerie backdrop. (This is an automatically generated summary.)s
Release date is 2022-02-04
Roger Frank and Sue Clark. (This file was produced from images generously made available by The Internet Archive)
Keywords: Short stories; Ghost stories; Man-woman relationships -- Fiction